Pengaruh Aktifitas Alat Berat dan Peledakan Terhadap Stabilitas Lereng Timbunan Tambang Batubara - Fanteri Aji Dharma Suparno; Siti Aminah; Haeruddin Haeruddin; Utari Retno Sulistyo Rini; Kurnia Dewi Mulyani; Emanuel Grace Manek; Muhammad Akbar Assyarbini (MEDIA KOMUNIKASI TEKNIK SIPIL, 2025)
Open-pit mining generates voids backfilled with overburden, forming artificial slopes susceptible to landslides. Improper slope design and external factors such as heavy equipment loads, blasting vibrations, and groundwater may trigger instability. This study examines the stability of a disposal slope adjacent to the blasting zone at PT X Coal Mine in East Kalimantan, Indonesia. The research uses secondary data from PT X. including geotechnical parameters and operational details, Slope stability was evaluated via the Limit Equilibrium Method (Bishop and Morgenstern-Price) and Finite Element Method (FEM). Initial analyses revealed critical safety factors (FoS) of 0.853 (Bishop, Morgenstern-Price) and 0.520 (FEM), indicating high instability under combined dynamic and hydrogeological stresses. A slope redesign was proposed, improving FoS to 3.932 (dry) and 3.523 (wet) via Limit Equilibrium, and 1.570 (dry) and 1.370 (wet) via FEM. These value;s comply with the safety threshold (FoS ≥ 1.1) specified in KEPMEN ESDM No. 1827 K/30/MEM/2018, ensuring operational safety. The study underscores the necessity of integrating geotechnical and operational constraints in slope design to mitigate landslide risks in open-pit mining.